1969
DOI: 10.4315/0022-2747-32.12.480
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Survival of Salmonella in Cheddar and Colby Cheese1

Abstract: Factors affecting the growth and survival of salmonellae in the experimental manufacture of 7 lots of Colby and 65 lots of' Cheddar cheese were studied. Milk was artificially contaminated just prior to making of cheese. Manufacturing variables tested included effects of milk pasteurization, size of starter inoculum, titratable acidity and cheese pH, type of lactic culture, chemical additives, salt and moisture content, supplemental cheese microorganisms, and curing temperatures. The rate and amount of acid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…This adaptation plus possible salt tolerance may explain the variability in counts within and between treatments after brining. As in the present study on Gouda and in previous work with other cheese types, Salmonella populations can survive (46) and even increase (20,25,26,42) during the initial stages of the manufacturing process of some cheeses in addition to the approximately 10-fold increase resulting from curd entrapment. In mozzarella cheese, despite initial growth during manufacturing, Salmonella levels are reduced substantially if not completely eliminated during stretching and molding, when internal temperatures can reach 80°C or higher (20).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This adaptation plus possible salt tolerance may explain the variability in counts within and between treatments after brining. As in the present study on Gouda and in previous work with other cheese types, Salmonella populations can survive (46) and even increase (20,25,26,42) during the initial stages of the manufacturing process of some cheeses in addition to the approximately 10-fold increase resulting from curd entrapment. In mozzarella cheese, despite initial growth during manufacturing, Salmonella levels are reduced substantially if not completely eliminated during stretching and molding, when internal temperatures can reach 80°C or higher (20).…”
Section: Resultssupporting
confidence: 86%
“…Other than these studies, data on the survival of pathogens in Gouda are scant. The majority of Salmonella challenge studies in cheese have been conducted using Cheddar cheese as a model (25,26,47,54,67). Because survival of pathogens, including Salmonella, in cheese differs with changes in manufacturing and aging conditions and resulting differences in physicochemical characteristics, comparisons should be made with caution.…”
Section: Counts (Mean ± Sem) O F Multidrug-resistant (Mdr) Salmonelmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant studies for the US FDA showed that Cheddar cheese produced from pasteurized milk inoculated with the following pathogens can survive for up to: 434 days for healthy Listeria monocytogenes, inoculated to contain 5 × 10 2 cells·mL −1 [55]; 270 days (with an average of 195 days for all the experimental condition) for mixed species of Salmonella (S. typhimurium, S. senftenberg 775W, S. New brunswick 1608 and S. Newport) inoculated with 3-5 × 10 2 cells·mL −1 [22]; and 158 days for E. coli O157:H7 inoculated with 1 × 10 3 cells·mL −1 [52]. These studies put in the question the adequacy of the 60-day holding period at ≥ 1.7°C [37].…”
Section: The 60 Days Aging Rolementioning
confidence: 99%
“…Shrestha et al (2011) found that the population of Salmonella 52 gradually decreased over time at storage temperatures of 4, 10, and 21 °C in Cheddar cheese with salt concentrations (0.7% and 1.8%) at different pH ranges (5.1 to 5.5). Hargrove, McDonough, and Mattingly (1969) found that salt did not enhance the inhibition of Salmonella in Cheddar or Colby cheeses made with a salt content of 1.8, 2.01, and 2.63%, a lactic starter of 0.5, 1, 2, and 3%, and a final pH of 5.0, 5.2, 5.4, and 5.7. Only pH and starter cultures were directly related to Salmonella inhibition.…”
Section: Resultsmentioning
confidence: 99%